Giải phương trình (3x-1)(2x-3)(2x-3)(x+5)=0

Question

Giải phương trình
(3x-1)(2x-3)(2x-3)(x+5)=0

in progress 0
Serenity 1 năm 2021-10-16T01:48:33+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-10-16T01:50:12+00:00

    (3x-1)(2x-3)(2x-3)(x+5)=0

    ⇔$\left \{ {{3x-1=0} \atop {2x-3=0}} \right.$⇔ $\left \{ {{3x=1} \atop {2x=3}} \right.$⇔ $\left \{ {{x=\frac{1}{3} } \atop {x=\frac{3}{2} }} \right.$ 

    $x+5=0⇔x=-5$

    Vậy $x=\frac{1}{3}$ , $x=\frac{3}{2}$$,x=-5$ 

    0
    2021-10-16T01:50:29+00:00

    (3x-1)(2x-3)(2x-3)(x+5)=0

    ⇒ (3x-1) =0 hoặc (2x-3) = 0 hoặc (x+5)=0

    ⇒ x= $\frac{1}{3}$ hoặc x= $\frac{3}{2}$ hoặc x= (-5)

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )